1, 3-Dibromo-5, 5-dimethylhydantoin mediated oxidative amidation of terminal alkenes in water. Issue 46 (16th November 2017) - Ma, Chunhua; Fan, Guojie; Wu, Ping; Li, Zhi; Zhou, Yang; Ding, Qingjie; Zhang, Wei
Abstract : A variety of terminal alkenes were converted to the corresponding amides in yields of 25 to 86% in water via treatment with 1, 3-dibromo-5, 5-dimethylhydantoin, followed by reaction with molecular iodine and aq. NH3 (or amine) in one pot. Abstract : A variety of terminal alkenes were converted to the corresponding amides in yields of 25 to 86% in water via treatment with 1, 3-dibromo-5, 5-dimethylhydantoin, followed by reaction with molecular iodine and aq. NH3 (or amine) in one pot. This metal- and organic solvent-free protocol is not only suitable for styrene derivatives, but also, for the first time, works well on terminal aliphatic alkenes.